Aqueous two-phase extraction of polysaccharides from Selaginella doederleinii and their bioactivity study. (July 2022) - Li, Gang; Ma, Xiankui; Jiang, Yongmei; Li, Weiwei; Wang, Yongling; Liu, Li; Sun, Chengxin; Xiao, Shiji; Lan, Jie; Kuang, Juxiang; Wang, Gang
Abstract: In this study, the ethanol/salt aqueous two-phase system was firstly used to extract Selaginella doederleinii polysaccharides (SDP). Through single factor and response surface analysis, the best extraction conditions were as follows: extraction time of 40 min, ultrasonic power of 280 W, ethanol concentration of 35%, inorganic salt concentration of 0.22 g/mL, and liquid/solid ratio of 25 mL/g with optimal predicted yield of 9.85%. The preliminary structure of SDP was analyzed by HPLC, SEM, Congo red experiment, FT-IR NMR, SEM, thermogravimetric analysis and XRD. In vitro antioxidant experiments indicated that SDP exhibition a potential antioxidant activity and the scavenging rate of SDP (120 μg/mL) against DPPH +·, ABTS +· and ferrous ions were 39.35%, 43.25% and 48.63%, respectively. Also, SDP had certain antitumor activity and the IC50 of SDP on A549 cells and HCT-116 cells were 1528 μg/mL and 2341 μg/mL, respectively. Graphical Abstract: ga1 Highlights: S. doederleinii polysaccharide (SDP) was extracted by aqueous two-phase system. The optimum extraction process of SDP was gained. The structure of SDP was characterization. SDP has excellent antioxidant and anti-tumor activity.